Strategi TI untuk Meningkatkan Inovasi Balitbangda Kota Palembang Menggunakan Ward and Peppard - Lioe, Valencia; Pratama, Dicky (Universitas Multi Data Palembang, 2025)
Information technology (IT) strategic planning plays an important role in improving the efficiency, effectiveness, and competitiveness of Balitbangda. This study developed an IT strategic plan to support research and innovation data management using the Ward and Peppard framework. The analysis was conducted through Value Chain, PEST, SWOT, and McFarlan Strategic Grid. The results of the study indicate that Balitbangda can improve operational efficiency through integrated applications, improving HR competencies, and optimizing IT infrastructure. The main challenges include budget constraints, lack of coordination between agencies, and low external participation. The proposed strategy includes the development of an administrative information system, HR training, and collaboration with research institutions and universities. The implementation of this strategy is expected to improve data management efficiency, support evidence-based decision-making, and strengthen the role of Balitbangda as a regional innovation center.